Management of Thematic Learning in Fostering Student Creativity in Early Children Education in Garut District - Aja Aja; Iim Wasliman; Nanang Hanafiah; Daeng Arifin (International Journal of Nusantara Islam, 2019)
In fact, early childhood education management in the field is still far from fulfilling the needs according to national education standards because basically the institution organizing PAUD service activities departs from a concern for early childhood education, therefore education carried out in PAUD units in the implementation of PAUD institutions experiences various obstacles. which can affect the continuity of educational activities, especially in the implementation of learning activities that become obstacles in the management of thematic learning in early childhood education units, including the lack of infrastructure, low qualifications and competence of educators, minimal finance, parents' understanding of early childhood education, efforts to improve learning outcomes. maximum systematically in education management including program planning, program implementation and program evaluation. This study aims to examine thematic learning management in fostering student creativity. In particular, this study aims to examine the planning, implementation, evaluation, problems, and solutions of learning in the development of student creativity. The research method used is descriptive qualitative method. This research was conducted using three data collection techniques regarding the results of research activities, namely interviews, observation and documentary studies. The theory underlying this research is George Robert Terry's theory, which is about POAC (Planning, organizing, actuating, and controlling). The results of research carried out on this occasion at the Prosperous Family Planning Institution and TK Plus Prima Insani Garut district have generally carried out thematic learning activities in fostering student creativity which refers to Permendikbud No. 137/2014 and Permendikbud No. 146/20014 by compiling planning, organizing, implementing and good control, in accordance with the prevailing regulations, both the management of its human resources and its facilities or infrastructure.